Pengembangan Teori dan Praktek Akuntansi Syariah Di Indonesia - Rabiahaladawiyah Rabiahaladawiyah; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Accounting practice in Indonesia initially only implemented a conventional-based accounting system, but over time with the majority of Indonesian people adhering to Islam this led to the emergence of sharia accounting in Indonesia, because the system taught by Islam requires a system that is fair, honest, and avoids from usury. This is inversely proportional to conventional accounting which contains ribawi elements in it, for this reason the development of sharia accounting theory and practice is very important to educate the public that sharia accounting is a solution for Islamic communities in complying with and implementing Islamic Shari'a. This research uses descriptive analysis method in its preparation, so this study aims to explain some important points related to sharia accounting practice and theory in Indonesia. Thus, the sharia accounting theory studied by the author aims to maintain Allah's sharia both conceptually and practically.